2011
DOI: 10.1016/j.ajhg.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in VPS35, Encoding a Subunit of the Retromer Complex, Causes Late-Onset Parkinson Disease

Abstract: To identify rare causal variants in late-onset Parkinson disease (PD), we investigated an Austrian family with 16 affected individuals by exome sequencing. We found a missense mutation, c.1858G>A (p.Asp620Asn), in the VPS35 gene in all seven affected family members who are alive. By screening additional PD cases, we saw the same variant cosegregating with the disease in an autosomal-dominant mode with high but incomplete penetrance in two further families with five and ten affected members, respectively. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
693
1
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 798 publications
(707 citation statements)
references
References 37 publications
7
693
1
6
Order By: Relevance
“…16 Over the last few years, many studies have shown the value of exome sequencing for gene discovery purposes in neurological disorders. [19][20][21][22][23] Next-generation sequencing technologies have also accelerated gene discovery in patients with dHMN, 9,24 CMT 25,26 or other inherited neuropathies. [27][28][29] More recently, the use of exome sequencing for diagnostic purposes in genetic disorders with a high degree of genetic heterogeneity such as CMT is being explored.…”
Section: Discussionmentioning
confidence: 99%
“…16 Over the last few years, many studies have shown the value of exome sequencing for gene discovery purposes in neurological disorders. [19][20][21][22][23] Next-generation sequencing technologies have also accelerated gene discovery in patients with dHMN, 9,24 CMT 25,26 or other inherited neuropathies. [27][28][29] More recently, the use of exome sequencing for diagnostic purposes in genetic disorders with a high degree of genetic heterogeneity such as CMT is being explored.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of DNAJC13 function in endosomal trafficking is evident from several studies showing alterations in trafficking of well-known retromer cargos when its function is perturbed (13,20). The function of retromer itself is linked to PD through the observation that mutations in another retromer subunit, VPS35, can cause familial parkinsonism (6,7). Immunofluorescence and co-immunoprecipitation studies show endogenous VPS35 co-localizes with DNAJC13 in mouse primary cortical neuron cultures (Supplementary Material, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two other genes [Leucine-rich repeat kinase 2 (LRRK2)/PARK8 and vacuolar protein sorting 35 ortholog (VPS35)] were since conclusively associated with autosomal dominant (AD) and four [parkin/PARK2, PTEN-induced kinase 1 (PINK1)/PARK6, DJ-1/PARK7, ATP13A2/PARK9] with early-onset autosomal recessive (AR) PD (Corti et al, 2011;Vilariño-Güell et al, 2011;Zimprich et al, 2011). Recently, mutations in eukaryotic translation initiation factor 4-gamma (EIF4G1)/PARK18 was reported as a probable cause of AD late-onset PD (Chartier-Harlin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%